Optimization of Adaptive Received Signal Strength Threshold Value by Using Particle Swarm Optimization in Long Term Evolution-Advanced (LTE-A) Network - Zainali, Muhammad Aiman; Yusof, Azita Laily; Ali, Mohd Tarmizi; Ya’acob, Norsuzila; Rosdi, Mastura; Ali, Mohd Saufi Nasro (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
Mobility management plays an important role in mobile network to support seamless communication in Long Term Evolution -Advanced (LTE-A) network. The important part in communication is handover execution. To provide seamless communication system, the handover execution for the user from one base station to the others must be done in a smooth way. Thus, there is a need to develop some techniques to the system to improve the handover execution. One of the problems in the existing network is the fixed handover threshold value. In this work, a framework has been proposed to analyze the handover performance as the speed and summation of handoff signaling and Radio Link Failure (RLF) timer varies due to poor radio conditions case. A mathematical equation has been derived from the proposed framework. From the result, it has been found that the proposed framework was able to identify the value of dynamic threshold value (Sath), which is the adaptive received signal strength (RSS) for handover.